Environmental aspects of the urban soils transformation under artificial surface - Гаврюшова, О. Є. (Man and Environment. Issues of Neoecology, 1970)
One of the characteristics of urban soils is the presence of sealed soils - soil under artificial turf. Determined value of the increase in urban areas and the effects of the « sealing»" of soil , the main problems concerning the distribution of sealed surfaces in urban areas in terms of land use change Proposes action on the part of state and local government.